VOLLEYBALL OUTDOOR GAMES - Ghairat Kurbanov; Sulaymanov Qurbanali; Redjapov O’tkir (American Journals, 2023)
Volleyball is accompanied by a high level of physical activity, sharp movements, teamwork skills and the ability to play the ball between several players play an important role. All of these skills require regular practice, the main one being practice games between the two teams. But too monotonous workouts can introduce a routine component into the sport, so it may be advisable to add elements of simpler games with elementary rules to them.
Keywords: Flight of the ball, Quick passes, passes to the captain, rapid passes, Volleyball pass relay, volleyball shooting, try, carry away, circular bast shoes, relay race with volleyball elements, oncoming volleyball passing over the net.